26.8k views
2 votes
Solve equation 3x-8(2x+3)= -6(2x+5)

User Kenrogers
by
5.0k points

2 Answers

4 votes

Answer:

x = 6

Explanation:

User Squgeim
by
4.3k points
3 votes

Answer:

x =6

Explanation:


3x-8(2x+3)= -6(2x+5)\\\\\mathrm{Expand}\:-8\left(2x+3\right):\quad -16x-24\\3x-16x-24=-6\left(2x+5\right)\\\\\mathrm{Add\:similar\:elements:}\:3x-16x=-13x\\-13x-24=-6\left(2x+5\right)\\\\\mathrm{Expand\:}-6\left(2x+5\right):\quad -12x-30\\-13x-24=-12x-30\\\\\mathrm{Add\:}24\mathrm{\:to\:both\:sides}\\-13x-24+24=-12x-30+24\\\\Simplify\\-13x=-12x-6\\\\\mathrm{Add\:}12x\mathrm{\:to\:both\:sides}\\-13x+12x=-12x-6+12x\\\\Simplify\\-x=-6\\\\\mathrm{Divide\:both\:sides\:by\:}-1\\


(-x)/(-1)=(-6)/(-1)\\\\Simplify\\\\x =6

User Wayne Chiu
by
6.1k points